Pengembangan Sistem Informasi Keuangan (Studi Kasus : KB & TK Permata Iman Malang) - Muhammad Rizsky; Satrio Agung Wicaksono; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Play Group & Kindergarten Permata Iman is a private educational institution established in 2005 and located in Malang city. One of the work units of Play Group & Kindergarteen Permata Iman is the financial section operated by the treasurer and monitored directly by the principal in relation to management record of fund, disbursement of funds, recap for each recording fund and make monthly financial report. Problems that occur in the funding process when the principal not present in the school because of some errand, causing the long wait for the fund request to disbursement the fund. For the financial recording process, the treasurer conducts all income recaps and disburses funds based on the notes that have been collected and recorded before by the treasurer. Resulting in considerable time and effort before recapture results before it can be reported to the principal each month. Based on these conditions, a Financial Information System developed by researchman was developed to facilitate the operational activities of financial units. Financial information systems provide funding facilities, recording of funds, and delivery of financial report monthly. Software development method used to develop this information system is using waterfall model. Then to test the results will be blackbox testing with method validation testing, user acceptance testing and compability testing. Validation testing result got valid on all 9 test case, user acceptance testing got 94.6% for all criteria, and compability got 2 critical error, 2 major and 7 minor issues.